Cyanine‐Anchored Silica Nanochannels for Light‐Driven Synergistic Thermo‐Chemotherapy. Issue 6 (23rd November 2016) - Deng, Yibin; Huang, Li; Yang, Hong; Ke, Hengte; He, Hui; Guo, Zhengqing; Yang, Tao; Zhu, Aijun; Wu, Hong; Chen, Huabing
Abstract : Smart nanoparticles are increasingly important in a variety of applications such as cancer therapy. However, it is still a major challenge to develop light‐responsive nanoparticles that can maximize the potency of synergistic thermo‐chemotherapy under light irradiation. Here, spatially confined cyanine‐anchored silica nanochannels loaded with chemotherapeutic doxorubicin (CS‐DOX‐NCs) for light‐driven synergistic cancer therapy are introduced. CS‐DOX‐NCs possess a J ‐type aggregation conformation of cyanine dye within the nanochannels and encapsulate doxorubicin through the π–π interaction with cyanine dye. Under near‐infrared light irradiation, CS‐DOX‐NCs produce the enhanced photothermal conversion efficiency through the maximized nonradiative transition of J ‐type Cypate aggregates, trigger the light‐driven drug release through the destabilization of temperature‐sensitive π–π interaction, and generate the effective intracellular translocation of doxorubicin from the lysosomes to cytoplasma through reactive oxygen species‐mediated lysosomal disruption, thereby causing the potent in vivo hyperthermia and intracellular trafficking of drug into cytoplasma at tumors. Moreover, CS‐DOX‐NCs possess good resistance to photobleaching and preferable tumor accumulation, facilitating severe photoinduced cell damage, and subsequent synergy between photothermal and chemotherapeutic therapy with tumor ablation. These findings provide new insights of light‐driven nanoparticles for synergistic cancer therapy. Abstract : Spatially confined cyanine‐anchored silica nanochannels possessing a J ‐type aggregation conformation of cyanine dye within the nanochannels and encapsulating chemotherapeutic doxorubicin through π–π interaction with cyanine dye for light‐driven synergistic cancer therapy are introduced.